ANALISIS PERANAN KEBIJAKAN PAJAK PENJUALAN ATAS BARANG MEWAH (PPnBM) DALAM MENGENDALIKAN IMPOR MOBIL (Studi pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean Tanjung Perak Surabaya) - Abd. Basit; Nur Diana; Affifudin Affifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT               This research aims to determine the role of the sales tax policy on luxury goods in controlling imports of cars. This study uses a descriptive qualitative approach. In 2013 Indonesia exported 170 thousand units of cars and imported 120 thousand units of cars. This condition requires the control of Indonesian people's consumption of imported cars. In the case of imposition of on motorized vehicles, the government issued a policy namely Government Regulation Number 22 of 2014 concerning Taxable Goods that are luxuriously classified in the form of Motor Vehicles which are subject to Sales Tax on Luxury Goods. The existence of policy on imported cars is expected to reduce public consumption of imported cars. The Tanjung Perak Port, which is the second largest port, has become the place of international and national trade traffic, this is evident from the many export and import activities that occur there. Tanjung Perak Port is a place for importing motorized vehicles through customs routes. Keywords: Value Added Tax on Luxury Goods, Policy, Control, Import.